Gastrogastric fistula: a case report of a rare late complication after Roux-en-Y gastric bypass - Santos, Anita; Costa, Santos; Costa, Washington; Pinto, Rui; Peixoto, Inês; Araújo, Rita; Alpoim, Carlos; Santos, Teresa (International Surgery Journal, 2025)
Gastrogastric fistula (GGF) is an uncommon complication after Roux-en-Y gastric bypass (RYGB) which may lead to several adverse outcomes. Patients may be asymptomatic, present with non-specific symptoms, or present initially with a complication. A high index of clinical suspicion is required for diagnosis. Treatment options may vary, but ultimately surgery remains the standard of care. A 48-year-old male with a history of RYGB presented to the emergency department with upper gastrointestinal bleeding. Upper endoscopy revealed a gastrogastric fistula but no active bleeding source. The patient developed haemorrhagic shock, and a second endoscopy identified a marginal bleeding ulcer in addition to the fistula; endoscopic haemostasis was achieved. After stabilization, the patient underwent surgery - remnant gastrectomy and refashioning of the gastrojejunal anastomosis. This case highlights a rare complication of bariatric and metabolic surgery – GGF following RYGB, with a severe initial presentation. Prompt diagnostic evaluation and adequate treatment are necessary to improve patient outcomes, which may otherwise be unfavourable.